Changes to the Madden‐Julian Oscillation in Coupled and Uncoupled Aquaplanet Simulations With 4xCO2 - Hien X. Bui (American Geophysical Union (AGU), 2020)
Abstract The impacts of rising carbon dioxide (CO2) concentration and ocean feedbacks on the Madden‐Julian Oscillation (MJO) are investigated with the Community Atmospheric Model Version 5 (CAM5) in an idealized aquaplanet configuration. The climate response associated with quadrupled CO2 concentrations and sea surface temperature (SST) warming are examined in both the uncoupled CAM5 and a version coupled to a slab ocean model. Increasing CO2 concentrations while holding SST fixed produces only small impacts to MJO characteristics, while the SST change resulting from increased CO2 concentrations produces a significant increase in MJO precipitation anomaly amplitude but smaller increase in MJO circulation anomaly amplitude, consistent with previous studies. MJO propagation speed increases in both coupled simulations with quadrupling of CO2 and uncoupled simulations with the same climatological surface temperature warming imposed, although propagation speed is increased more with coupling. While climatological SST changes are identical between coupled and uncoupled runs, other aspects of the basic state such as zonal winds do not change identically. For example, climate warming produces stronger superrotation and weaker mean lower tropospheric easterlies in the coupled run, which contributes to greater increases in MJO eastward propagation speed with warming through its effect on moisture advection. The column process, representing the sum of vertical moist static energy (MSE) advection and radiative heating anomalies, also supports faster eastward propagation with warming in the coupled run. How differing basic states between coupled and uncoupled runs contribute to this behavior is discussed in more detail.